Controls-based approach for evaluation of information security standards implementation costs - Olifer, Dmitrij; Goranin, Nikolaj; Kaceniauskas, Arnas; Cenys, Antanas (Technological and Economic Development of Economy, 2017)
According to the PricewaterhouseCoopers analysis, the average cost of a single information security and data protections breaches has increased twice during 2015 (Pricewaterhouse Coopers 2015). Amount of organizations who reported serious breach has also risen (from 9% in 2015 to 17% in 2016) (PricewaterhouseCoopers 2016). To achieve their goals criminals are using different techniques starting from Social engineering (phishing, whaling) and finishing with malware execution (such as ransomware) on target machines. Recent attacks (attack on Central Bank of Bangladesh, fraud attack on Mattel CEO and attack on Thailand state-run Government bank ATM) show, that criminals are very well organized, equipped and spend a lot of money and time to prepare their attacks. To protect themselves organizations are required to ensure security in depth principles and implement complex Security solutions, which are able to ensure the needed level of information security in appropriate costs.However, information security cost-benefits assessment is complicated, because of lack of structured cost-benefit methods and issues with comparing IT security solutions in light of prevailing uncertainties. Existing methods are oriented on processes, environment lifecycles or specific standard implementations. Because of that, existing methods do not cover all needed security areas and methods reusability is a complicated task. Trying to solve this issue, we have proposed a new method for information standards implementation costs evaluation, based on information security controls.